Religious Challenges to Anti-Discrimination Law: The Mobilization of the “Minority Label” - Brière-Godbout, Léa; Plante, Marie-Andrée (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2020)
In 2018, the American and Canadian supreme courts released two high-profile decisions: the case of a Christian baker from Colorado who refused to create a cake for the celebration of a same-sex couple’s union, and the case of an evangelical Christian law school in British Columbia whose code of conduct prohibiting same-sex intimacy led to accreditation refusals by three provincial law societies. In both cases, religious believers argued that modern LGBTQ2+ anti-discrimination protections required them to act in ways that proved incompatible with their religious beliefs. While such “conflict of rights” are familiar to liberal democracies, this article demonstrates how these cases operate within a new paradigm in which religious actors, seeking exemptions from legal protections accorded to a vulnerable minority, claim minority status for themselves. Hoping to have their policy agenda seen in a new light, such opponents of LGBTQ2+ rights have replaced their discourse defending traditional mores with one arguing that the broadly cherished value of pluralism guarantees them a religious right to “dissent” from anti-discrimination protections. We dub this discursive process the mobilization of the “minority label.”In this article, we retrace the emergence of this new discourse by turning to the narratives crafted by parties, courts, and media in the two cases. We discuss the three main argumentative strategies through which the minority label manifests in discourses: language framing, moral symmetry arguments, and respectability claims.We then offer a comparative analysis which explores the different ways both courts reacted to this discourse. We conclude with a brief discussion of some of the long-term risks that the rise of such a discourse implies for LGBTQ2+ rights.